A Fenton-like cation can improve arsenic trioxide treatment of sclerodermatous chronic Graft-versus-Host Disease in mice - Chêne, Charlotte; Jeljeli, Mohamed Maxime; Rongvaux-Gaïda, Dominique; Thomas, Marine; Rieger, François; Batteux, Frédéric; Nicco, Carole (Frontiers in Immunology, 2022)
Graft-versus Host Disease (GvHD) is a major complication of hematopoietic stem cell transplant. GvHD is characterized by the chronic activation of immune cells leading to the development of systemic inflammation, autoimmunity, fibrosis and eventually death. Arsenic trioxide (ATO) is a therapeutic agent under clinical trial for the treatment of patients with systemic lupus erythematosus (SLE) and chronic GvHD (cGvHD). This therapy is admittedly rather safe although adverse effects can occur and may necessitate short interruptions of the treatment. The aim of this study was to combine ATO with a divalent cation, to generate a Fenton or Fenton-like reaction in order to potentiate the deletion of activated immune cells through the reactive oxygen species (ROS)-mediated effects of ATO in a mouse model, and thereby enabling the use of lower and safer ATO concentrations to treat patients with cGvHD. In vitro, among the various combinations of divalent cations tested, we observed that the combination of ATO and CuCl2 (copper chloride) induced a high level of oxidative stress in HL-60 and A20 cells. In addition, this co-treatment also decreased the proliferation of CD4+ T lymphocytes during a mixed lymphocyte reaction (MLR). In vivo, in a cGvHD mouse model, daily injections of ATO 2.5 µg/g + CuCl2 0.5 µg/g induce a decrease in lymphocyte activation and fibrosis that was equivalent to that induced by ATO 5 µg/g. Our results show that the addition of CuCl2 improved the effects of ATO and significantly limited the development of the disease. This co-treatment could be a real benefit in human patients to substantially decrease the known ATO side effects and optimize ATO treatment in pathologies characterized by activated cells sensitive to an increase in oxidative stress.